Inflammation as a key mediator: linking triglyceride-glucose index to prognosis in non-muscle-invasive bladder cancer - Zhang, Yan; Li, Zixiang; Shao, Xianfeng; Jiang, Shan; Wang, Jiahao; Zhang, He; Chen, Li; Ding, Li; Wang, Kun; Xia, Wentao; Wang, Junqi (Frontiers in Oncology, 2025)
BackgroundBladder carcinoma (BCa) is a prevalent urological malignancy characterised by high recurrence and progression rates, posing significant challenges in clinical management. The triglyceride-glucose (TyG) index has emerged as a promising prognostic marker for metabolic health in various cancers. This study explores the prognostic value of the TyG index in non-muscle-invasive bladder cancer (NMIBC), with a focus on its association with high-grade recurrence-free survival (RFS) and progression-free survival (PFS) and the mediating role of systemic inflammation.MethodsA total of 230 patients diagnosed with NMIBC between October 2017 and October 2022 were included in this retrospective study. Clinical and pathological data were collected alongside follow-up treatment outcomes. Mediation analysis was conducted to quantify the role of systemic inflammation, using markers such as C-reactive protein (CRP), interleukin-6 (IL-6), and interleukin-8 (IL-8), in the relationship between the TyG index and patient prognosis.ResultsThe TyG index was identified as a significant, non-linear prognostic factor for both RFS and PFS. An inverted U-shaped relationship was observed, with inflexion points at 9.186 and 9.168 for RFS and PFS, respectively. Below these thresholds, the TyG index was positively associated with worse outcomes (RFS: HR = 3.37, 95% CI = 1.77–6.41, P < 0.001; PFS: HR = 3.54, 95% CI = 1.65–7.58, P = 0.001). Mediation analysis revealed systemic inflammation as a critical intermediary, contributing significantly to the observed associations.ConclusionThese findings suggest that the TyG index could serve as a valuable tool for risk stratification and prognostic assessment in NMIBC. Its integration into clinical decision-making frameworks may improve personalised management strategies, particularly by targeting systemic inflammation as a modifiable factor.